THE IMPACT OF DISCLOSURE OF ISLAMIC CORPORATE SOCIAL RESPONSIBILITY OF EACH INDIVIDUAL DIMENSIONS ON PROFITABILITY - Muhamat Romadhoni; Sylva Alif Rusmita (Jurnal Ekonomi Syariah Teori dan Terapan, 2021)
ABSTRAKPenelitian ini mempunyai tujuan untuk mengetahui dampak dari pengungkapan secara dimensi individu laporan Islamic Corporate Social Responsibility (ICSR) terhadap profitabilitas dalam bank umum syariah. Dalam penelitian ini digunakan pendekatan kuantitatif dengan metode regresi data panel serta dengan bantuan alat statistik yaitu Eviews 9. Terdapat 10 bank umum syariah di Indonesia pada periode 2016-2020 yang dijadikan sebagai sampel dalam penelitian ini. Pengukuran pengungkapan ICSR dilakukan dengan teknik konten analisis berdasarkan item-item yang mendeskripsikan nilai-nilai Islam pada laporan tahunan bank sehingga menghasilkan indeks pengungkapan Index Social Reporting (ISR). Hasil dari pengujian hipotesis menunjukkan bahwa secara simultan pengungkapan ICSR berpengaruh positif signifikan terhadap profitabilitas bank umum syariah. Secara parsial, pengungkapan dimensi per individu ICSR tidak mempunyai hubungan yang signifikan secara statistik antara dimensi individu ICSR terhadap profitabilitas, kecuali untuk ‘komitmen terhadap karyawan’, ‘komitmen terhadap debitur’, dan ‘komitmen terhadap komunitas’.Kata Kunci: Pengungkapan, Islamic Corporate Social Responsibility, Profitabilitas, Bank Umum Syariah. ABSTRACTThis study aims to determine the impact of the disclosure of individual dimensions of Islamic Corporate Social Responsibility (ICSR) reports on profitability in Islamic commercial banks. In this study, a quantitative approach was used with the panel data regression method and with the help of a statistical tool, namely Eviews 9. There were 10 Islamic commercial banks in Indonesia in the 2016-2020 period which were used as samples in this study. The measurement of ICSR disclosure is carried out using content analysis techniques based on items that describe Islamic values in the bank's annual report so as to produce a disclosure index of the Index Social Reporting (ISR). The results of hypothesis testing indicate that simultaneously the disclosure of ICSR has a significant positive effect on the profitability of Islamic commercial banks. Partially, the disclosure of individual dimensions of ICSR does not have a statistically significant relationship between individual dimensions of ICSR on profitability, except for 'commitment to employees', 'commitment to debtors', and 'commitment to community'.Keywords: Disclosure, Islamic Corporate Social Responsibility, Profitability, Islamic Commercial Banks.DAFTAR PUSTAKAChariri, A., & Ghozali, I. (2007). Teori akuntansi. Semarang: Badan Penerbit Universitas Diponegoro.Ahmad, N. N. N., & Sulaiman, M. (2004). Environment Disclosures in Malaysian Annual Reports: A Legitimacy Theory Perspective. International Journal of Commerce and Management, 14(1), 44-58. https://doi.org/10.1108/10569210480000173Aribi, Z. A., & Arun, T. (2015). Corporate social responsibility and Islamic financial institutions (IFIs): Management perceptions from IFIs in Bahrain. Journal of Business Ethics, 129(4), 785–794.Aribi, Z. A., & Gao, S. S. (2012). Narrative disclosure of corporate social responsibility on Islamic financial institutions. Managerial Auditing Journal, 27(2), 199–222.Arshad, R., Othman, S., & Othman, R. (2012). Islamic corporate social responsibility, corporate reputation and performance. World Academy of Science, Engineering and Technology, 64, 1070–1074.Asutay, M. (2007). Conceptualisation of the secondbest solution in overcoming the social failure of Islamic banking and finance: Examining the overpowering of homoislamicus by homoeco- nomicus. IIUM Journal of Economics and Management, 15(2), 167–195.Athanasoglou, P. P., Brissimis, S. N., & Delis, M. D. (2008). Bank- specific, industry-specific and macroeconomic determinants of bank profitability. Journal of International Financial Markets, Institutions and Money, 18, 121–136.Barnett, M. L., & Salomon, R. M. (2012). Does it pay to be really good? Addressing the shape of the relationship between social and financial performance. Strategic Management Journal, 33, 1304–1320.Baydoun, N., & Willet, R. (1997). Islam and accounting: Ethical issues in the presentation of financial information, accounting, commerce and finance. The Islamic Perspective, 1(1), 1-25.Beerli, et al. (2004). A model of customer loyalty in the retail banking market. European Journal of Marketing, vol. 38.Buckingham, G., Gregory, A., & Whittaker, J. (2011). Do markets value corporate social responsibility in the United Kingdom? Retrieved July 17, 2013 from http://business-school.exeter.ac.uk/ documents/papers/finance/2011/1107.pdf.Burke, L. and Logsdon, J. M. (1996). How Corporate Social Responsibility Pays Off. Long Range Planning, 29(4), 495-502. https://doi.org/10.1016/0024-6301(96)00041-6Bourke, P. (1999). Concentration and other determinants of bank profitability in Europe, North America and Australia. Journal of Banking & Finance, 13, 65–79.Chambers, C.L., & Day, R. (2009). The Banking sector and CSR: An unholy alliance. Financial Regulation International, 12(9), 1-7.Chronopoulos, D. K., Liu, H., McMillan, F. J., & Wilson, J. O. S. (2013). The dynamics of US bank profitability. Retrieved from http://ssrn.com/abstract=1972835.Demirguc-Kunt, A., & Huizinga, H. (2000). Financial structure and bank profitability. Policy Research Working Paper Series 2430. The World Bank.Donaldson, T., & Preston, L. E. (1995). The stakeholder theory of the corporation: Concepts, evidence, and implications. The Academy of Management Review, 20(1), 65–91.Evangelinos, K.I., Skouloudis, A., Nikolaou, I.E., & Filho, W. L. (2009). An analysis of corporate social responsibility (CSR) and sustainability reporting assessment in the Greek banking sector. In S.O. Idowu & W. L. Filho (Eds.), Professionals’ perspectives of corporate social responsibility (pp. 157-177). London, New York: Springer.Farag, H., Mallin C., & Ow-Yong K. (2014). Corporate social responsibility and financial performance in Islamic banks. Journal of Economic Behavior and Organization, 103(July 2014), S21-S38. https://doi.org/10.1016/j.jebo.2014.03.001.Fishman, R., Heal, G., & Nair, V. (2005). Corporate social responsibility: Doing well by doing good? Working Paper. University of Pennsylvania.Fitria, Soraya., & Hartanti. (2010). Islam dan tanggung jawab sosial: Studi perbandingan pengungkapan berdasarkan global reporting initiative indeks dan Islamic social reporting indeks. Simposium Nasional Akuntansi XIII, Purwokerto.Gao, L., & Zhang, J. (2013). Firms’ earnings smoothing, corporate social responsibilities, and valuation. Journal of Corporate Finance, 32(June 2015), 108-127Ghozali, I. (2007). Manajemen risiko perbankan. Semarang: Badan Penerbit Universitas Diponegoro..Gray, et al. (1995). Accounting and accountability: Changes and challenges in corporate social and environment reporting. London: Prentice Hall Europe.Haniffa, R., & Hudaib, M. (2007). Exploring the ethical identity of Islamic banks. Journal of Business Ethics, 76, 97–116.Hassan, M. K., Rashid, M., Imran, Md Y, & Shahid, A. I. (2010). Ethical gaps and market value in the Islamic banks of Bangladesh. Review of Islamic Economics, 14(1), 49–75.Hillman, A. J., & Keim, G. D. (2001). Shareholder value, stakeholder management, and social issues: What’s the bottom line? Strategic Management Journal, 22, 125–139.Juliansyah, N. (2011). Metode penelitian kualitatif. Jakarta: Kencana Prenada Media Group.Kapopoulos, P., & Lazaretou, S. (2007). Corporate ownership structure and firm performance: Evidence from Greek firms. Corporate Governance: An International Review, 15(2), 144–158.Kementrian Agama Republik Indonesia. (2021). Al Qur’an dan terjemahannya. Jakarta: Kemenag RI.Kosmidou, K. (2008). The determinants of banks’ profits in Greece during the period of EU financial integration. Managerial Finance, 34(3), 146–159.Kuncoro, M. (2011). Metode kuantitatif. Yogyakarta: Sekolah Tinggi Ilmu Manajemen YKPN.Maali, B., Casson, P., and Napier, C. (2013). Social reporting by Islamic banks. Abacus, 42(2): 266-289.Mahoney, L., & Roberts, R. W. (2007). Corporate social performance, financial performance and institutional ownership in Canadian firms. Accounting Forum, 31, 233–253.Mahoney, L., & Thorne, L. (2005). Corporate social responsibility and long-term compensation: Evidence from Canada. Journal of Business Ethics, 57(3), 241–253.Makni, R., Francoeur, C., & Bellavance, F. (2009). Causality between corporate social performance and financial performance: Evidence from Canadian firms. Journal of Business Ethics, 89, 409–422.Mallin, C., Farag, H., & Ow-Yong, K. (2014). Corporate social responsibility and financial performance in Islamic   banks. Journal of Economic Behavior & Organization, 103, S21–S38.Sulaiman, Maliah. (2010). Tessting A Model of Islamic Corporate financial Reports: Some Experimental Evidence. The International Islamic University Malaysia. IIUM Journal of Economics and Management, 9(2), 115-39.Marom, I. Y. (2006). Toward a unified theory of the CSP–CFP link. Journal of Business Ethics, 67, 191–200.McGuire, J. B., Sundgren, A., & Schneeweis, T. (2008). Corporate social responsibility and firm financial performance. Academy of Management Journal, 21, 854–872.Meutia, Inten. (2010). Shariah enterprise theory sebagai dasar pengungkapan tanggung jawab sosial untuk bank syariah. Disertasi tidak diterbitkan. Malang: Universitas Brawijaya.Platonova, E., Asutay M., Dixon R., & Mohammad S. (2018). The impact of corporate social responsibility disclosure on financial performance: Evidence from the GCC Islamic banking sector. Journal Business Ethics, 151, 451-471. https://doi.org/10.1007/s10551-016- 3229-0.Prabowo, R. (2015). Analisis beban kerja untuk menentukan jumlah karyawan optimal (Studi kasus: PT. Sanjayatama Lestari Surabaya). Skripsi tidak diterbitkan. Surabaya: ITATS.Preston, L. E., & O’Bannon, D. P. (1995). The corporate social financial performance relationship: A typology and analysis. Business Society, 36, 419–429.Purwanto, A. (2011). Pengaruh tipe industri, ukuran perusahaan, profitabilitas, terhadap corporate social responsibility. Jurnal Akuntansi & Auditing, 8(1), 1-94.Roberts, R. W. (2012). Determinants of corporate social responsibility disclosure: An application of stakeholder theory. Accounting, Organisations and Society, 17(6), 595-612.Scholtens, B. (2009). Corporate social responsibility in the international banking industry. Journal of Business Ethics, 86, 159-175.Simpson, W. G., & Kohers, T. (2002). The link between corporate social and financial performance: Evidence from the banking industry. Journal of Business Ethics, 35, 97–109.Short, B. K. (1999). The relation between commercial bank profit rates and banking concentration in Canada, Western Europe and Japan. Journal of Banking and Finance, 3, 209–219.Steers, R., & Porter, L. W. (2011). Motivation and work behavior, New. York: Academic Press.Untung, H. B. (2008). Corporate social responsibility. Jakarta: Sinar Grafika.Waddock, S. A., & Graves, S. B. (1997). The corporate social performance—financial performance link. Strategic Management Journal, 18(4), 303–319.